FEATURES OF THE USE OF SOCIO-POLITICAL WORDS IN THE KARAKALPAK LANGUAGE(ON THE EXAMPLE OF FOLK EPICS) (The Role of Exact Sciences in the Era of Modern Development, 2025)
This thesis examines the scope of socio-political words used effectively in the language of folk epics and analyzes the current significance of such words.